2011
DOI: 10.1177/1367006911425816
|View full text |Cite
|
Sign up to set email alerts
|

Balanced communication in mid-infancy promotes early vocabulary development: effects of play with mother and father in mono- and bilingual families

Abstract: In this longitudinal study on Finnish and Finnish-Russian families, infants’ play interaction at 7 months with each parent was observed during 5-minute play sessions ( N = 96) and predictive relations between co-regulated communication in mid-infancy and language development at 14 months were examined. Parental differences in communication were greater within the culturally diverse Finnish-Russian families than within the culturally less diverse Finnish families. Four family-level communication profiles were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…In addition, DLL infants/toddlers’ conceptual vocabularies (i.e., the number of vocabulary concepts known in their two languages combined) are the same size as monolinguals’ vocabularies (Junker & Stockman, 2002; Lundén & Silvén, 2011; Pearson, Fernández, & Oller, 1993), with some overlap in the words/concepts known in both languages. It has been suggested that the degree of overlap in young children’s vocabularies may be greater when the children’s two languages are typologically related, resulting in the similarity in forms of words across the two languages (Schelletter, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DLL infants/toddlers’ conceptual vocabularies (i.e., the number of vocabulary concepts known in their two languages combined) are the same size as monolinguals’ vocabularies (Junker & Stockman, 2002; Lundén & Silvén, 2011; Pearson, Fernández, & Oller, 1993), with some overlap in the words/concepts known in both languages. It has been suggested that the degree of overlap in young children’s vocabularies may be greater when the children’s two languages are typologically related, resulting in the similarity in forms of words across the two languages (Schelletter, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…A similar advantage in recognizing words (receptive vocabulary) showed up already at 14 months (Lundén & Silvén, 2011). Studies based on English and Spanish, have shown that bilinguals do not lag behind monolinguals in total vocabularies (Hoff et al, 2012;Pearson et al, 1997).…”
Section: Bilingual and Monolingual Vocabulary Growthmentioning
confidence: 86%
“…The two groups of families were largely comparable with respect to mothers' and fathers' age, education, and employment (see Table 1; for more details, see Lundén & Silvén, 2011). The fathers of the monolingual families were, on average, four years younger than the fathers of the bilingual families.…”
Section: Participantsmentioning
confidence: 97%
“…For example, differences in infants’ perception of intentional agency at 12 months predicts their understanding of others’ theory of mind, mental states, and beliefs as 4-year-olds (Yamaguchi, Kuhlmeier, Wynn, & vanMarle 2009). Infants’ interactions at 7 months predict their expressive and productive vocabulary at 14 months (Lunden & Silven 2011). Infants whose mothers show positive responses at 12 months have higher WPPSI IQ at 4 years (Pearson et al 2011); and fathers’ diverse vocabulary in interactions with their infants at 6 months predicts children’s communication skills at 15 months, after adjusting for infant developmental level at 6 months and other confounders (Pancsofar & Vernon-Feagans 2010).…”
Section: Stability and Prediction From Infancymentioning
confidence: 99%